Rationale and design of a randomised clinical trial for an extended cardiac rehabilitation programme using telemonitoring: the TeleCaRe study. Issue 1 (December 2016) - Snoek, Johan; Meindersma, Esther; Prins, Leonie; van't Hof, Arnoud; Hopman, Maria; de Boer, Menko-Jan; de Kluiver, Ed
Abstract Background Despite the known positive effects of cardiac rehabilitation and an active lifestyle, evidence is emerging that it is difficult to attain and sustain the minimum recommendations of leisure time physical activity. The long-term benefits are often disappointing due to lack of adherence to the changes in life style. Qualitative research on patients' perspectives suggests that motivation for lifestyle change tends to diminish around 3 months after the index-event. The time most cardiac rehabilitation programmes end. The aim of the present study is to determine if prolongation of a traditional cardiac rehabilitation programme with additional heart rate based telemonitoring guidance for a period of 6 months results in better long term effects on physical and mental outcomes, care consumption and quality of life than traditional follow-up. Methods In this single centre randomised controlled trial 120 patients with an absolute indication for cardiac rehabilitation will be randomised in a 1:1 ratio to an intervention group with 6 months of heart rate based telemonitoring guidance or a control group with traditional follow-up after cardiac rehabilitation. The primary endpoint will be VO2peak after 12 months. Secondary endpoints are VO2peak after 6 months, quality of life, physical-, emotional- and social functioning, cardiac structure, traditional risk profile, compliance to the use of the heart rate belt and smartphone, MACE and care-consumption. Discussion The TeleCaRe study will provide insight into the added value of the prolongation of traditional cardiac rehabilitation with 6 months of heart rate based telemonitoring guidance. Trial registration Dutch Trial Register:NTR4644 (registered 06/12/14).